Multimolecular tracers of terrestrial carbon transfer across the pan‐Arctic: 14C characteristics of sedimentary carbon components and their environmental controls. Issue 11 (2nd November 2015) - Feng, Xiaojuan; Gustafsson, Örjan; Holmes, R. Max; Vonk, Jorien E.; van Dongen, Bart E.; Semiletov, Igor P.; Dudarev, Oleg V.; Yunker, Mark B.; Macdonald, Robie W.; Wacker, Lukas; Montluçon, Daniel B.; Eglinton, Timothy I.
Abstract: Distinguishing the sources, ages, and fate of various terrestrial organic carbon (OC) pools mobilized from heterogeneous Arctic landscapes is key to assessing climatic impacts on the fluvial release of carbon from permafrost. Through molecular 14 C measurements, including novel analyses of suberin‐ and/or cutin‐derived diacids (DAs) and hydroxy fatty acids (FAs), we compared the radiocarbon characteristics of a comprehensive suite of terrestrial markers (including plant wax lipids, cutin, suberin, lignin, and hydroxy phenols) in the sedimentary particles from nine major arctic and subarctic rivers in order to establish a benchmark assessment of the mobilization patterns of terrestrial OC pools across the pan‐Arctic. Terrestrial lipids, including suberin‐derived longer‐chain DAs (C24, 26, 28 ), plant wax FAs (C24, 26, 28 ), and n ‐alkanes (C27, 29, 31 ), incorporated significant inputs of aged carbon, presumably from deeper soil horizons. Mobilization and translocation of these "old" terrestrial carbon components was dependent on nonlinear processes associated with permafrost distributions. By contrast, shorter‐chain (C16, 18 ) DAs and lignin phenols (as well as hydroxy phenols in rivers outside eastern Eurasian Arctic) were much more enriched in 14 C, suggesting incorporation of relatively young carbon supplied by runoff processes from recent vegetation debris and surface layers. Furthermore, the radiocarbon content of terrestrial markers is heavily influenced by specific OC sources and degradation status. Overall, multitracer molecular 14 C analysis sheds new light on the mobilization of terrestrial OC from arctic watersheds. Our findings of distinct ages for various terrestrial carbon components may aid in elucidating fate of different terrestrial OC pools in the face of increasing arctic permafrost thaw. Key Points: Molecular 14 C content of multiple terrestrial markers is compared in pan‐arctic sediments Suberin‐ and cutin‐derived diacids trace old and young terrestrial carbon separately New light is shed on terrestrial carbon sources and mobilization pathways in arctic basins